Current challenges in secondary progressive multiple sclerosis: diagnosis, activity detection and treatment - Brieva, Luis; Calles, Carmen; Landete, Lamberto; Oreja-Guevara, Celia (Frontiers in Immunology, 2025)
Approximately 50% diagnosed with relapsing-remitting multiple sclerosis (RRMS) transition to secondary progressive multiple sclerosis (SPMS) within 20 years following disease onset. However, early diagnosis of SPMS and effective treatment remain important clinical challenges. The lack of established diagnostic criteria often leads to delays in identifying SPMS. Also, there are limited disease-modifying therapies (DMTs) available for progressive forms of MS, and these therapies require evidence of disease activity to be initiated. This review examines the challenges in diagnosing SPMS at an early stage and summarizes the current and potential use of biomarkers of disease progression in clinical practice. We also discuss the difficulties in initiating the DMTs indicated for active SPMS (aSPMS), particularly in patients already undergoing treatment with DMTs that suppress disease activity, which may mask the presence of inflammatory activity required for the therapy switch. The article also addresses the DMTs available for both active and non-active SPMS, along with the clinical trials that supported the approval of DMTs indicated for aSPMS or relapsing MS in Europe, which includes aSPMS. We also offer insights on when discontinuing these treatments may be appropriate.